Development Prospects of Education System in Russia - E. A. Yarnykh; L. A. Davletshina; G. V. Agentova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies the situation in the education system ofRussiaand lines of upgrading this system in view of country economy rising to a new stage of development, i.e. digitalization of all economic processes. As information technologies grow, unskilled labour becomes a thing of the past and is being replaced by intellectual labour. A lot of specialties that can be replaced by workers using digital technologies are neglected by labour market. The key goal of higher school today is to develop concepts of new specialties, which in its turn requires designing of new programs of teaching, competences, curriculums, etc. Upgrading the education system should be carried out on the basis of all positive achievements of the past. The authors present statistic measurement of education processes and identify stages of transformations and reforms of the education system. Education is a part of our life, which in the future can prove, whether our society will be prosperous and life standard of people will change.